2015
DOI: 10.1177/1066896915594881
|View full text |Cite
|
Sign up to set email alerts
|

A Peripheral Dentinogenic Ghost Cell Tumor With Immunohistochemical Investigations and a Literature Review–Based Clinicopathological Comparison Between Peripheral and Central Variants

Abstract: The aim of the study was to present a peripheral dentinogenic ghost cell tumor (DGCT) and to describe clinicopathological differences between peripheral and central variants of the tumor using a selected literature review. The case report is based on a swelling present on the alveolar ridge of a 74-year-old edentulous denture wearer. The lesion was diagnosed as a peripheral DGCT after excluding the presence of a central lesion. Immunohistochemical investigations revealed similar cytokeratin expression pattern,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 17 publications
2
6
0
Order By: Relevance
“…Besides the importance to confirm the epithelial nature of GCONs, CKs expression can be important to understand the origin of these tumors, which remains unclear yet. CK7, CK14, and CK19 expression, as observed in some cases in our review, was previously reported in germinal dental tissues and other odontogenic tumors, reinforcing their odontogenic origin [4,60,61]. DGCTp was thought to arise from remnants of the dental lamina or alveolar mucosa surface epithelium [4,32], and the continuity of the basal layer with the tumor parenchyma was reported in 9 (17.3%) cases.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Besides the importance to confirm the epithelial nature of GCONs, CKs expression can be important to understand the origin of these tumors, which remains unclear yet. CK7, CK14, and CK19 expression, as observed in some cases in our review, was previously reported in germinal dental tissues and other odontogenic tumors, reinforcing their odontogenic origin [4,60,61]. DGCTp was thought to arise from remnants of the dental lamina or alveolar mucosa surface epithelium [4,32], and the continuity of the basal layer with the tumor parenchyma was reported in 9 (17.3%) cases.…”
Section: Discussionsupporting
confidence: 80%
“…DGCTp often appeared as mucosal firm painless nodular lesion measuring up to 3.0 cm, mimicking frequent reactive lesions of the oral mucosa [4,[30][31][32], being the main imaging finding, when present, a slight "cup-shaped" erosion of the underlying cortical bone [30,32]. A great clinical resemblance was noted between DGCTc and GCOC in this review.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…To date, only 18 cases of peripheral DGCTs with accompanying clinical and radiographic features have been reported [7,10,[29][30][31][32][33][34][35][36][37][38][39][40] ( Table 1). The DGCTs were found in patients over a wide range of ages from 13 to 83 years (mean, 56 years).…”
Section: Discussionmentioning
confidence: 98%
“…Two variants of DGCT, namely, central and peripheral, have been described [26]. Central DGCT, the more common of the two, is a locally invasive intraosseous tumor, whereas peripheral DGCT is a non-invasive extraosseous tumor [27]. In most cases of central DGCT, the radiographic features are unilocular with a mixture of radiolucent and radiopaque or only radiolucent lesions [3].…”
Section: Discussionmentioning
confidence: 99%